Histological changes in liver structure following a therapeutic and overdose administration of paracetamol in female mice. - A. Alrefadi, Mabrouka; Ahmad Engliez, Souad; Ahmad Engliez, Souad (Scientific Journal of University of Benghazi, 2026)
The effects of administration of two formulations of paractamol, (pandol formulation) PI and (calpol formulation) PII were studied on the female mice liver, using routine histological technique. The histological examination of the liver obtained from the animals received daily therapeutic dose of PI and PII drugs for one month showed vascular congestion and small focal areas of inflammatory cells associated with central vein and portal vein. In addition, enlarged hepatocytes, and some normal hepatocytes were observed to contain abundant microvesicles. On the other hand, the overdose administration caused intensive histological alterations in the liver. These changes included congested blood sinusoid, congested central vein and branch of portal vein. In addition, nuclear changes, necrotic cells were dispersed throughout the parenchyma, mild microvesicles and macrovesicles were also observed in hepatocytes.